The amidase domain of lipoamidase specifically inactivates lipoylated proteins in vivo. - Maroya D Spalding; Sean T Prigge (PLoS ONE)
Background In the 1950s, Reed and coworkers discovered an enzyme activity in Streptococcus faecalis (Enterococcus faecalis) extracts that inactivated the Escherichia. coli and E. faecalis pyruvate dehydrogenase complexes through cleavage of the lipoamide bond. The enzyme that caused this lipoamidase activity remained unidentified until Jiang and Cronan discovered the gene encoding lipoamidase (Lpa) through the screening of an expression library. Subsequent cloning and characterization of the recombinant enzyme revealed that lipoamidase is an 80 kDa protein composed of an amidase domain containing a classic Ser-Ser-Lys catalytic triad and a carboxy-terminal domain of unknown function. Here, we show that the amidase domain can be used as an in vivo probe which specifically inactivates lipoylated enzymes. Methodology/principal findings We evaluated whether Lpa could function as an inducible probe of alpha-ketoacid dehydrogenase inactivation using E. coli as a model system. Lpa expression resulted in cleavage of lipoic acid from the three lipoylated proteins expressed in E. coli, but did not result in cleavage of biotin from the sole biotinylated protein, the biotin carboxyl carrier protein. When expressed in lipoylation deficient E. coli, Lpa is not toxic, indicating that Lpa does not interfere with any other critical metabolic pathways. When truncated to the amidase domain, Lpa retained lipoamidase activity without acquiring biotinidase activity, indicating that the carboxy-terminal domain is not essential for substrate recognition or function. Substitution of any of the three catalytic triad amino acids with alanine produced inactive Lpa proteins. Conclusions/significance The enzyme lipoamidase is active against a broad range of lipoylated proteins in vivo, but does not affect the growth of lipoylation deficient E. coli. Lpa can be truncated to 60% of its original size with only a partial loss of activity, resulting in a smaller probe that can be used to study the effects of alpha-ketoacid dehydrogenase inactivation in vivo.